2016
DOI: 10.1155/2016/7053867
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Frontal Cortex in Standing Postural Sway Tasks While Dual-Tasking: A Functional Near-Infrared Spectroscopy Study Examining Working Memory Capacity

Abstract: Posture control during a dual-task involves changing the distribution of attention resources between the cognitive and motor tasks and involves the frontal cortex working memory (WM). The present study aimed to better understand the impact of frontal lobe activity and WM capacity in postural control during a dual-task. High and low WM-span groups were compared using their reading span test scores. High and low WM capacity were compared based on cognitive and balance performance and hemoglobin oxygenation (oxyH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 54 publications
5
44
0
3
Order By: Relevance
“…Mirelman et al (2014) had subjects stand still and perform serial seven subtractions, a common cognitive loading task, resulting in increased activation in the left and right frontal lobe compared to single-task standing. Fujita et al (2016) also observed increased brain activity in a cognitive DT paradigm using fNIRS. High and low memory span groups performed one or two leg standing with a Stroop task.…”
Section: Resultsmentioning
confidence: 92%
“…Mirelman et al (2014) had subjects stand still and perform serial seven subtractions, a common cognitive loading task, resulting in increased activation in the left and right frontal lobe compared to single-task standing. Fujita et al (2016) also observed increased brain activity in a cognitive DT paradigm using fNIRS. High and low memory span groups performed one or two leg standing with a Stroop task.…”
Section: Resultsmentioning
confidence: 92%
“…Studies suggest reduced gamma-aminobutyric acid B-mediated cortical inhibition27 and elevated muscular coactivation26,28 to be the primary reasons for this effect. Boisgontier et al,6 Ruffieux et al,26 and Smith et al29 in their review studies concluded that application of dual task on fall-prone population groups results in postural instability and poor cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…From a motor control perspective, the DLPFC has been implicated in postural control and balance (Fujita, Kasubuchi, Wakata, Hiyamizu, & Morioka, ; Mihara et al., ), such that the DLPFC is involved with integrating sensory cues and allocating attentional resources during postural control (Woollacott & Shumway‐Cook, ). Particularly related to aging, recent fNIRS studies have shown an age‐related reduction in effective (Huo et al., ) and functional connectivity (Wang et al., ) between the left and right DLPFC during postural changes between older and young adults.…”
Section: Introductionmentioning
confidence: 99%